Relationship of Parental and Adolescents' Screen Time to Self-Rated Health: A Structural Equation Modeling - Werneck, Andre O.; Silva, Danilo R.; Agostinete, Ricardo R. [UNESP]; Fernandes, Romulo A. [UNESP]; Ronque, Enio R. V.; Oyeyemi, Adewale L.; Cyrino, Edilson S. (Sage Publications Inc, 2018)
Aim. To investigate the association of parental and adolescents' screen time with self-rated health and to examine the mediating effects of psychosocial factors (social relationships and distress) on this association. Method. A cross-sectional study was conducted among 984 Brazilian adolescents (10- to 17-year-olds). Self-rated health, screen time (adolescents and parental), and perception of social relationships and distress were evaluated through self-report questionnaires. Structural equation modeling was adopted to investigate the pathways of the relationship between adolescents' screen time and self-rated health. Results. Adolescents' screen time was directly and negatively related to self-rated health only in boys (r = -0.158, p = .015). In girls, screen time was related to self-rated health through distress (r = -0.188, p = .007) and social relationships (r = 0.176, p = .008). The models fit was adequate ((2)/df 3.0, root mean square error of approximation <0.08, comparative fit index >0.90, and Tucker-Lewis Index >0.90). Conclusions. Higher screen time was associated with poor self-rated health in boys, while in girls, psychosocial factors mediated the adverse relationships between screen time and self-rated health.
Keywords: motor activity; physical activity; sedentary lifestyle